The Literary Coptic manuscripts in the A.S. Pushkin State Fine Arts Museum in Moscow - Elanskai︠a︡, A. I. 1926- (Vigiliae Christianae, Supplements, 1994)
This volume contains the first complete publication of the collection of Coptic literary manuscripts now in the A.S. Pushkin Fine Arts Museum, Moscow. The collection formed in 1870-1908 by Vladimir Golenischev is of great value since it covers almost the entire field of early Christian literature in Egypt and substantially aids to fill up serious lacunae in many well-known literary works, to say nothing of the texts hitherto unknown. Important is also the fact that Coptica Golenischeviana largely derives from the library of St. Shenoute's monastery at Sohag, this virtual National Library of Christian Egypt, the source of the riches of the museums and libraries of Paris, Vienna, Berlin et cetera.